(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
In 21th century, pedagogy tends to self-understanding of a human being. From this point of view as alternative means of approaches the art-technologies give opportunity to reveal a child comprehensively, find one’s inner troubles, support as a pedagogue-psychologists, make the child’s ability to socialize more constructive and to boost and to appropriate his moral criteria. Art-technologies impact better especially when they are based on the art of the pedagogical rules. Art-technologies are divided into several types. Depending on its artistic-aesthetic and creative aspects we do differentiate the following types of art-technology: Bibliotherapy Music therapy Drama-therapy Fairy tale- therapy Isotherapy As an art-technology Bibliotherapy is based on the power of speech and its powerful impact. Drama- therapy or an image-therapy is a way of the playful act, when one by one the importance is given to voice, stage behavior, etudes, imagination, the stage performance of the feelings and so on. For the Fairy tale- therapy are chosen several types of fairy tales. The fairy tale also helps to diagnose one’s different problems. Isotherapy promotes the biological creativity of a healthy person. It also decreases the problems of a child struggling development problems. One of the types of it is a picture, collage, sculpture, plasticine, artwork, and so forth. In its all ways the music therapy has its unique place in the frames of the art-technology. It helps a person to develop a stress resistance system, promotes the ways of the associative thinking, calms the system of the nerves, etc. It’s significant to highlighted readiness of an art-technology trainer as from his/her professional approach depends the final result of this art-technology and its positive outcome.